al-Qur'an dan tantangan modernitas - Maarif, Ahmad Syafii 1935-; Tuhuleley, Said.; Majid, Nurcholish, 1939-2005; Seminar Nasional Al-Qur'an dan Tantangan Modernitas (1989 : Universitas Muhammadiyah Yogyakarta) (Yogyakarta : Sipress, 1990)
Islam and modernization with reference to Indonesia; papers of seminar
Includes bibliographical references and index.
Keywords: Economic development -- Religious aspects -- Islam -- Congresses; Islam -- Economic aspects -- Indonesia -- Congresses; Islam -- 20th century -- Congresses; Indonesia -- Economic policy -- Congresses